2020
DOI: 10.1515/jpem-2019-0516
|View full text |Cite
|
Sign up to set email alerts
|

Estimations of total serum testosterone levels in Nigerian term neonates at birth using anogenital distance measurements

Abstract: BackgroundIn genital anomalies, measurement of total testosterone is required but is expensive and technically difficult to assay. Therefore, the measurement of anogenital distance, which is non-invasive and cheap, could be used to estimate total serum testosterone in neonates. The objective if this study is to determine the relationship between total serum testosterone and anogenital distance and estimate total serum testosterone levels in term neonates using measurements of anogenital distance.MethodsThis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…All the reagents were commercially obtained and the manufacturers' standard operating procedures were strictly observed Estradiol, luteinizing hormone, follicle-stimulating hormone, progesterone, and testosterone, were determined by enzymelinked immunosorbent assay using ACCUBIND ELISA kits as described by 23 , 24 , also DHEA by the enzyme-linked immunosorbent assay as described by 25 . Lipid peroxidation (malondialdehyde) was evaluated as described by 26 , while total antioxidant activity was determined as described by 27…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…All the reagents were commercially obtained and the manufacturers' standard operating procedures were strictly observed Estradiol, luteinizing hormone, follicle-stimulating hormone, progesterone, and testosterone, were determined by enzymelinked immunosorbent assay using ACCUBIND ELISA kits as described by 23 , 24 , also DHEA by the enzyme-linked immunosorbent assay as described by 25 . Lipid peroxidation (malondialdehyde) was evaluated as described by 26 , while total antioxidant activity was determined as described by 27…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…We divided the aims of the studies into five categories. First, two studies examined the associations between T and child health including autistic spectrum disorder (El-Baz et al, 2014;Kung et al, 2016), whereas nine studies examined the associations of T levels with child development including physical growth (bodyweight, length, body mass index, skinfold triceps) (Becker et al, 2015;Kiviranta et al, 2016), motor and language development (Cho et al, 2017;Whitehouse et al, 2012), pubertal transition (Mouritsen et al, 2014), anogenital distance in neonates (Avidime et al, 2011;Jain et al, 2018;Kareem et al, 2020), and postnatal activation of HPG axis after insulin injection (de Jong et al, 2012). The second category included the five studies that aimed to identify T measurements with greater accuracy and precision by comparing methods and materials (Ankarberg-Lindgren & Norjavaara, 2015;Contreras et al, 2017;Fang et al, 2017;Hamer et al, 2018;Knickmeyer et al, 2011).…”
Section: Problem Statements and Aims Of Selected Studiesmentioning
confidence: 99%
“…Mouritsen et al (2014) reported that pubertal transition-related serum T levels were quantifiable 1.5 years earlier by LC/MS rather than RIA, especially in boys. Avidime et al (2011), Jain et al (2018, and Kareem et al (2020) examined whether AGD was related to T levels in cord and postnatal blood. Avidime et al (2011) reported no gender differences in T levels measured by EIA between boys (2.78 + 0.30 ng/ml) and girls (2.09 + 0.22 ng/ml) as well as no correlation between AGD and T levels in both sexes.…”
Section: Study Findings Based On Study Aimsmentioning
confidence: 99%
See 1 more Smart Citation